2011
DOI: 10.3168/jds.2010-3811
|View full text |Cite
|
Sign up to set email alerts
|

Induced lactation in pubertal heifers: Efficacy, response to bovine somatotropin, and profitability

Abstract: Heifer rearing represents one of the largest costs of commercial dairying because these animals do not begin to produce milk until approximately 2 yr of age. The objectives of this study were to characterize milk production, growth, reproduction, and herd life after induced lactation in healthy 15-mo-old heifers. We further wanted to quantify their lactation response to bovine somatotropin (bST), and compare survival rate and profitability of heifers induced into lactation to that of heifers reared using tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 25 publications
5
29
1
5
Order By: Relevance
“…The success rates achieved in the current study are similar to those reported in previous studies [13,14]. The success rate for heifers (85%) was less than that (97%) reported previously [15]. The success rate for cows (71%) was somewhat lower than the 90% rate reported by Jewel [14].…”
Section: Lactation Induction Success Ratesupporting
confidence: 35%
See 1 more Smart Citation
“…The success rates achieved in the current study are similar to those reported in previous studies [13,14]. The success rate for heifers (85%) was less than that (97%) reported previously [15]. The success rate for cows (71%) was somewhat lower than the 90% rate reported by Jewel [14].…”
Section: Lactation Induction Success Ratesupporting
confidence: 35%
“…Kensinger [7] found it more profitable to induce lactation in non-breeder cows than to purchase replacement heifers or to cull non-lactating cows. However, Macrina et al [15] found no economic benefit in using lactation induction in heifers. The high fertility of dairy heifers in temperate regions in this last study might have led to the estimation of no beneficial effects of lactation induction.…”
Section: Economics Of Lactation Inductionmentioning
confidence: 99%
“…Lactation can be induced successfully in 15-mo-old dairy heifers; however, they produce less milk than postpartum animals (Smith and Schanbacher, 1974;Macrina et al, 2011b). This is not surprising considering they are much younger than postpartum heifers that calve at 24 to 25 mo of age.…”
Section: Introductionmentioning
confidence: 99%
“…Uma possível explicação pode ser pelo fato de estímulos incompletos provocados por hormônios exógenos injetáveis durante o PIL quando comparado a lactações não induzidas. Com isso é necessário maior período para o desenvolvimento da GM e dos alvéolos até atingir o pico de produção de leite (MELLADO et al, 2011;MACRINA et al, 2014;DELOUIS et al, 1978;HAYS, 1975;TOZER;. É possível observar também que o pico de produção de leite em novilhas é ainda mais lento quando comparado ao de vacas, o que deve se explicar pelas novilhas continuarem seu crescimento após o início da lactação (MAGLIARO et al, 2004;TOZER;.…”
Section: Produção De Leiteunclassified
“…No presente estudo, foram observados maiores teores de sólidos do leite (gordura, proteína e lactose) em comparação com resultados de Tozer;.…”
Section: Composição Do Leiteunclassified